Effects of plastic mulch film residues on soil-microbe-plant systems under different soil pH conditions. (March 2021) - Liu, Yin; Huang, Qing; Hu, Wen; Qin, Jiemin; Zheng, Yingrui; Wang, Junfeng; Wang, Qingqing; Xu, Yuxin; Guo, Genmao; Hu, Shan; Xu, Li
Abstract: Plastic mulch film residues (PMFR) accumulated throughout mulching years can result in serious environmental problems, especially in hotter areas with frequent farming (e.g. the tropics). The effects of long-term mulching on the soil-microbe-plant system, however, are largely unknown. As mulching years is positively correlated with PMFR concentrations, we used a controlled pot experiment to investigate the effects of mulching years (20a: The concentration of PMFR is about 2 g kg −1, 60a: About 6 g kg −1 ) on rice growth, rhizosphere bacterial communities, and soil organic carbon (SOC) under different soil pH conditions. Mulching years reduced rice growth; 20a showed more negative effects than 60a on rice tillers number and biomass. PMFR changed the composition, diversity, and metabolic function of the rhizosphere bacterial communities. The content of SOC decreased as mulching residues increased; total organic carbon (TOC), soil organic matter (SOM), Fn (355), and humification index (HIX) declined by 30.24%, 55.97%, 59.74%, and 70.24%, respectively. Furthermore, significant correlations between bacterial communities and SOC were observed in the soil-microbe-plant system. PMFR showed stronger negative effects on rice growth in acidic soil (pH 4.5); however, in basic soil (pH 8.5), there were stronger variations within the bacterial communities and a more significant decline in SOC than acidic soil (pH 4.5). The results of this study are expected to provide theoretical references for understanding of the effects of PMFR on agroecosystems and preventing and controlling plastic pollution. Graphical abstract: Image 1 Highlights: Plastic mulch film residues (PMFR) affect the rhizophere bacterial communities. Microbe significant correlations with SOM and SOC when response to PMFR. Negative effects of PMFR on rice growth were stronger under acidic conditions. SOC declined significantly more in alkaline soils with PMFR concentrations.